Características Agro-Socio-Ambientales de la Agricultura familiar Productora de Granos Andinos en el Barrio Colaya Pamba, Parroquia Aláquez, Cantón Latacunga, provincia de Cotopaxi. - Cunalata Toapaxi, Dorys Ivonne (2018)
The purpose of research was to determine the characteristics of the family agriculture that produce Andean grains at the Colaya Pamba neighborhood, Alaquez Parish, Cotopaxi Province. In it, a survey was compiled of the information of the practices carried out by the farmers, in the same way, primary information was generated on the climate perception and its influence on the crops, using the methodology of focal groups, and was compared with statistics the Instituto Nacional de Meteorología e Hidrología (INAMHI), With the data obtained it is evident that, climatic factors such as frost 72,.2%, and drought 90,9%, affect the crops in the study area. In the socioeconomic aspect, the main income source of the neighborhood is agriculture; the same one that presents a reduction of the system because 72,7% of the population migrates.In the analysis of the resources for the production, it was identified that the soil in the sector is sandy, with little fertility; in terms of production systems it was verified that 22,7% of the producers carried out crop rotation, 27,3% polyculture and 50% monoculture, especially in the corn (Zea mays), this practice has caused vulnerability ecological and affects the appearance of pests, diseases and their subsequent use of pesticides, which has generated unsustainability of the productive system of Andean grains in the neighborhood.